Substantiation of the scheme and parameters wide span vehicle - Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Aiubov, Abdulmelik; Аюбов, Абдулмелік Мухтарович; Аюбов, Абдулмелик Мухтарович (ФОП Однорог Т. В., 2019)
The article is devoted to the problems of the aggregation wide span vehicle. The plane-parallel movement of the wide span vehicle in the horizontal and vertical planes is investigated.
Keywords: controlled traffic farming; wide span tractor-based machine; theoretical research